Entrepreneurial failure, as a learning experience for entrepreneurs in the Municipality of Puebla, México (GEON Journal (Management, Organizations and Business), 2017)
When starting a new entrepreneurship project, corporate bankruptcy (failure) is one of the problems that most concern new entrepreneurs; since many efforts must be made with little progress. Taking into account the above for the following work, the measurement of the failure of Puebla's microentrepreneurs is made known. This is due to the fact that failure seems to be an inherent phenomenon of entrepreneurship and most of the microentrepreneurs fail to see a learning opportunity based on the mistakes made previously, which can subsequently generate better conditions to guarantee success in the opening of a company.Therefore, in order to measure the failure of Puebla's microentrepreneurs, firstly, the theory and methodology related to the subject of study is studied, and secondly, the results obtained from the surveys conducted in Puebla's micro-enterprises are presented. know the causes of failures, to finally generate some recommendations that allow the use of the generated information.
Keywords: Entrepreneurs; Failure; microentrepreneurs; financing